DIMENSIONS AND ELEMENTS OF PANCASILA STUDENT PROFILE IN QURANIC PERSPECTIVE YULPIA QURAN - Rachman, Wa Sree Galuatry; Ratna M, Ratna M (Jurnal Konseling Pendidikan Islam, 2025)
This research aims to examine the dimensions and elements of the Pancasila Student Profile from the Al-Quran perspective and answer the problem of whether there is a correlation between the dimensions and elements of the Pancasila Student Profile from the Al-Quran Perspective. This research uses a qualitative method with a content analysis approach to Al-Quran verses related to the values contained in the dimensions and elements of the Pancasila Student Profile. The results of the research show that there is a strong correlation between the dimensions and key elements of the Pancasila Student Profile and the teachings of the Al-Quran, namely having faith, being devoted to God Almighty, and having noble character, global diversity, independence, cooperation, critical reasoning, creativity which is in line with the teachings of the Al-Quran. -Quran. It is hoped that this research can contribute to the development of character education based on the values of Pancasila and the Al-Quran, as well as strengthening the moral and ethical foundations in the education process in Indonesia.